Effect of Antiviral Therapy for HCV on Lipid Levels. Issue 1 (January 2017) - Mauss, Stefan; Berger, Florian; Wehmeyer, Malte H; Ingiliz, Patrick; Hueppe, Dietrich; Lutz, Thomas; Simon, Karl G; Schewe, Knud; Rockstroh, Juergen K; Baumgarten, Axel; Christensen, Stefan
Background: HCV has complex interactions with human lipid metabolism leading to down regulation of cholesterol levels. Interferon (IFN) therapy has been shown to decrease cholesterol even further. With the availability of second-generation direct-acting antiviral agents (DAA) the effect of suppressing and eliminating HCV on lipid metabolism warrants reevaluation. Methods: Prospective German multicentre cohort on HCV- and HIV–HCV-infected patients treated with direct-antiviral agents (GECCO). Lipids were assessed at baseline, during and after therapy. Wilcoxon test corrected for multiple testing was used. Results: For the analysis, 520 patients with chronic hepatitis C were available. Patients with chronic hepatitis C were treated as follows: sofosbuvir (SOF)/pegylated IFN (PEG-IFN)/ribavirin (RBV; HCV=34, HIV–HCV=36), SOF/ RBV (HCV=47, HIV–HCV=16), SOF/simeprevir (HCV=9, HCV–HIV=2), SOF/daclatasvir +/- RBV (HCV=27, HIV–HCV=47), SOF/ledipasvir +/- RBV (HCV=147, HCV–HIV=100) and ombitasvir/paritaprevir/ritonavir +/-dasabuvir +/- RBV (2D, HCV=2, HCV–HIV=6; 3D, HCV=39, HCV–HIV=8). On treatment there was a statistically significant increase in total cholesterol for any IFN-free DAA regimen, which was maintained after end of therapy. Changes of total cholesterol were driven by changes in low-density lipoprotein cholesterol, whereas high-density lipoprotein cholesterol remained unchanged. In contrast, total cholesterol decreased on SOF/PEG-IFN/RBV and increased after end of therapy above baseline levels. Triglycerides increased during treatment with SOF/PEG-IFN/RBV, but not on DAA-only regimens. Conclusions: Suppressing and eliminating HCV with IFN-free DAA regimens increased cholesterol levels, but had no effect on triglycerides. In contrast IFN-based therapy decreased cholesterol and increased triglycerides during treatment and led to increases in cholesterol after achieving sustained virological response.